BS EN 61009-1 CORR1. Residual current operated circuit-breakers with integral overcurrent protection for household and similar uses (RCBOs). Annex N. Additional requirements and tests for RCBOs consisting of one residual current protection function and several independent two-pole overcurrent protection functions. (27th March 2020) - British Standards Institution,
No abstract available